Investigation of peripheral inflammatory biomarkers in association with suicide risk in major depressive disorder - Pethő, Borbála; Kovács, Márton Áron; Simon, Diána; Tóth, Tünde; Hajnal, András Sándor; Csulak, Tímea; Hebling, Dóra; Albert, Noémi; Varga, Eszter; Herold, Márton; Osváth, Péter; Vörös, Viktor; et al. (Frontiers in Psychiatry, 2024)
Suicide is the most severe complication of major depressive disorder (MDD). Novel research assumes the role of immunological dysregulation in the background – several studies have reported alterations in the number of inflammatory cells related to both MDD and suicidality. There are currently no objective, routinely measured parameters to indicate suicidal vulnerability. However, altered inflammatory cell numbers and ratios have been proposed as potential biomarkers of suicide risk (SR). The present research aims to examine changes of these values related to increased SR in MDD as an assumed inflammatory state. We investigated laboratory parameters of psychiatric in-patients diagnosed with MDD (n = 101) retrospectively. Individuals with recent suicide attempt (SA) (n = 22) and with past SA (n = 19) represented the high SR group. MDD patients with no history of SA (n = 60) composed the intermediate SR group. We compared the number of neutrophil granulocytes, monocytes, lymphocytes, platelets, white blood cell count (WBC), neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte ratio (PLR), mean platelet volume (MPV), red blood cell distribution width (RDW) and erythrocyte sedimentation rate (ESR). Furthermore, we evaluated alterations of these parameters related to antidepressant (AD) and antipsychotic (AP) treatment, which have been proved to have anti-inflammatory effects. We found a significant increase in neutrophil granulocyte count, NLR, monocyte count, MLR, WBC and ESR in patients with recent SA compared to patients with no history of SA. Moreover, there was a significant elevation in monocyte count, MLR, ESR and RDW in patients with high SR compared to patients with intermediate SR. AD treatment resulted in a significant decrease in neutrophil granulocyte count and NLR, however, it did not affect monocyte count and MLR. Assuming immunological mechanisms in the background of MDD and suicidality, our findings support the role of NLR as a biomarker of acute SR, though its alterations may be masked by possible anti-inflammatory effects of AD treatment in the long term. However, MLR, a marker exhibiting changes which are not attenuated by pharmacotherapy, may be a possible indicator of both acute and long-term suicidal vulnerability.